Structure and logical organization of current studies in track and field sports - V.I. Bobrovnik (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to develop a system of assessment and prediction of technical skill athletes-athletes. Material : the study involved 450 athletes qualifications. Results : in the process of preparing members of the Ukrainian national team implemented a system of assessment of mental state. It includes: a set of informative indicators biomechanical laws and their changes; biomechanical model of motor actions; technology operational biomechanical modeling, changes in the functional state of the viscoelastic properties of skeletal muscle vestibulomotornoy system and speed- force readiness, evaluation and prediction of physical condition of athletes qualified. And complex pedagogical tests and scorecards. For the evaluation of the functional state of the autonomic nervous, cardiovascular system, external respiration system by analyzing the electrocardiogram, heart rate variability, the definition of autonomic balance, state of the myocardium, cardiac arrhythmias, spirometric studies, system performance evaluation of the athlete in extreme conditions by identifying the type and properties of temperament, level of personal anxiety and psychological evaluation reliability athletes. Conclusions : the structure and logical organization of modern studies of different primary focus, based on the assessment of technical skills, physical fitness, functional and mental state of highly skilled athletes.